Iudex qui iuravit sibi non liquere - Zabłocki, Jan (Prawo Kanoniczne, 1996)
In the 2nd century B.C. in ancient Rome it was not required of the judges that they were conversant with the law. Every Roman citizen who had certain social status could be enroled on album iudiciorum selectorum. In The Attic Nights (Gell. 14.2) Gellius describes how after being chosen by the paetors among the iudices he sought texts in Greek as well as Latin on duties of a judge. But in complicated cases and in doubts engendered by conflicting opinions, such books simply could not help him. Aulus Gellius mentions one problem that was presented to him and that was a real conundrum. Namely a sun of money was claimed before him which was said to have been paid and counted out (pecunia non numerata) but the plaintiff did not support his case by witness, relying only on slender arguments. However, it was clear that he was on unimpeachable moral character while the defendant had a questionable reputation and was often convicted of mendacity, full of treachery and fraud. Since Gellius did not want to reach verdict precipitately, he consulted some friends of great legal experience. They had no doubt that the defendant should be acquitted and that it was no use retarding the proceedings since the plaintiff could not produce the legal evidence required (either expensilatio, mensae rationes, chirographum, tabulae obsignatae or testes). But Gellius knew well that if he had returned a verdict of not guilty, the plaintiff would have been subject to iudicium de calumnia. Therefore author of The Attic Nights didn’t feel satisfied and consulted Favorinus, a well-know philosopher. The latter proceeded to discuss various aspects of a judge’s function. He pondered, for instance, whether a judge should reach to verdict on the basis of his full knowledge or only in accordance with what has been brought up during the trial. In the end Favorinus advised Gellius a decision in favour of the plaintiff on the ground of his creditable character. Nevertheless Gellius could not make up his mind and accordingly took oath mihi non liquere and in that way he was relieved from rendering a decision.